Parents’ understanding of early writing development and ways to promote it: Relations with their own children’s early writing - Aram, Dorit; Yashar, Rony (Frontiers in Education, 2023)
The study examined how parents' understanding of early writing development was reflected in how they analyzed anonymous preschool children's writings and the support they offered to promote these children's writing. It also assessed how this general knowledge related to their own children's early writing development. The participants were 274 parents and one of their children (M = 5.4 years old). During home visits, the parents were shown vignettes with three writing samples of invitations to a party written by anonymous 5½-6-year-old preschoolers. The sample represented initial, intermediate, and advanced early writing levels. The parents were asked to relate to each of these vignettes and write what the child who wrote the invitation knows about writing and how they would recommend promoting the child. Additionally, the participating parents' children's early writing was assessed. We studied the parents' references to the following literacy aspects: Letters, orthography (e.g., final letters, vowel letters), phonology, and the writing system (e.g., the direction of writing, the separation between words) when relating to the vignettes and when recommending ways to support the children's writing development. The study’s analyses revealed that parents distinguished between the writing levels of these anonymous children and suggested providing writing support recommendations in line with the various levels. Parents mainly referred to the letters when describing and suggesting support for the initial writing level. They referred more to the writing system when giving their opinion and suggesting support for the writing at an advanced level. The more parents referred to different aspects of literacy when analyzing the writing vignettes, the more aspects of writing support they suggested in their writing support recommendations. Parents who related to more literacy aspects in their writing support recommendations to anonymous children had children with higher writing levels. The study indicates that parents' general knowledge and understanding of literacy development has a role in fostering their own children’s literacy skills.